Stratospheric Influence on Baroclinic Lifecycles and its Connection to the Arctic Oscillation ... - Wittman, Matthew A. H.; Polvani, Lorenzo M.; Charlton, Andrew J.; Scott, Richard K. (Columbia University, 2004)
Using an idealized primitive equation model, we investigate how stratospheric conditions alter the development of baroclinic instability in the troposphere. Starting from the lifecycle paradigm of Thorncroft et al., we consider the evolution of baroclinic lifecycles resulting from the addition of a stratospheric jet to the LC1 initial condition. We find that the addition of the stratospheric jet yields a net surface geopotential height anomaly that strongly resembles the Arctic Oscillation. With the additional modification of the tropospheric winds to resemble the high-AO climatology, the surface response is amplified by a factor 10 and, though dominated by the tropospheric changes, shows similar sensitivity to the stratospheric conditions. ...